2002
DOI: 10.1093/embo-reports/kvf119
|View full text |Cite
|
Sign up to set email alerts
|

A role for endogenous glucocorticoids in wound repair

Abstract: Exogenous glucocorticoids are known to inhibit wound repair, but the roles and mechanisms of action of endogenous glucocorticoids during the healing process are as yet unknown. Therefore, we wounded mice expressing a DNA-binding-defective mutant version of the glucocorticoid receptor (GR dim mice) and also analysed fibroblasts from these animals in vitro. We found a remarkably enlarged granulation tissue with a high fibroblast density in GR dim mice. This difference is likely to result from an increased migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 15 publications
6
38
0
Order By: Relevance
“…Steroids potently suppress the local and systemic inflammatory response in GR dim mice, and repression of AP-1 and NF-κB-dependent genes, such as matrix metalloproteinase-3 and collagenase-3, is comparable to wild-type mice [48,49,50]. Indeed, analysis of GR dim mice has recently provided insight into the mechanism of impaired wound repair [51]. After skin injury there is enhanced granulation tissue and increased numbers of fibroblasts in GR dim mice as compared to control, suggesting that the inhibitory effect of steroids on wound healing is mediated by the DNA binding activity of GR (see Table 1).…”
Section: Transcriptional Modulation By Gr: Dna Binding Vs Protein-prmentioning
confidence: 99%
“…Steroids potently suppress the local and systemic inflammatory response in GR dim mice, and repression of AP-1 and NF-κB-dependent genes, such as matrix metalloproteinase-3 and collagenase-3, is comparable to wild-type mice [48,49,50]. Indeed, analysis of GR dim mice has recently provided insight into the mechanism of impaired wound repair [51]. After skin injury there is enhanced granulation tissue and increased numbers of fibroblasts in GR dim mice as compared to control, suggesting that the inhibitory effect of steroids on wound healing is mediated by the DNA binding activity of GR (see Table 1).…”
Section: Transcriptional Modulation By Gr: Dna Binding Vs Protein-prmentioning
confidence: 99%
“…Effective cell-matrix communication is crucial for efficient wound healing. Several nuclear hormone receptors, one of the largest known classes of transcription factors, have been implicated wound repair (8,9). Of interest, studies have shown that nuclear hormone receptor peroxisome proliferator-activated receptor ␤/␦ (PPAR␤/␦) is an early transcription factor that modulates keratinocyte response to inflammation during wound healing (10,11).…”
mentioning
confidence: 99%
“…However, when the analysis of GR dim mice was expanded to other inflammatory processes, we observed a failure of GCs to exert a full anti-inflammatory response. This was the case for exogenous actions of GCs in contact allergy and for the modulatory role of endogenous GCs in septic shock and for the early response during wound healing exhibiting elevated cytokine and chemokine expression (Grose et al, 2002;Tuckermann et al, 2007). As a side effect GC inhibition of bone formation occur in these mice.…”
Section: Resultsmentioning
confidence: 99%
“…) Wound healing like in wild type; but delayed kinetik (Grose et al, 2002) Hepatic GH activity controlling body growth like in wild type A c c e p t e d M a n u s c r i p t…”
Section: Phenotypes Of Pharmacological Gc Administration In Gr Dim Micementioning
confidence: 99%
See 1 more Smart Citation